Impact of multidisciplinary tumor boards on patients with rectal cancer - Ioannidis, Argyrios (Mol Clin Oncol, 2018)
Οncological outcomes in patients with primary rectal cancer have markedly improved over the last few years, mainly due to the widespread application of the total mesorectal excision technique. This improvement should also be largely attributed to multiple specialties, other than colorectal surgery, such as radiology, oncology and pathology. Therefore, a multimodal approach is key to efficient and appropriate rectal cancer management. Multidisciplinary tumor (MDT) boards have become an important asset for the management and treatment of patients with rectal cancer, and a number of studies published to date suggest the beneficial effect of the multidisciplinary approach on the management of such patients. The available evidence demonstrates a modification of the treatment plan, attributed to the MDT implementation, in a non-negligible proportion of these patients. However, more studies are required in order to assess the exact impact of MDT boards on disease-free and overall survival of patients with primary rectal cancer.